The Religious Phenomenon comprehended from the opening to transcendence: posibility or limit? A critical look from Charles Taylor’s thought - Sepúlveda del Río, Ignacio (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
There are different ways to understand and to define religion. The Canadian philosopher Charles Taylor —who has been working the religious phenomenon during the last years— has tried to define religion through transcendence. This definition is not exempt of difficulties and critics: one of them focuses on the idea that religion proposes too high human ideals such as asceticism, mortification or the renounce to the ordinary objectives of human life. The second critic focuses on the idea that religion is not able to assume and recognize violence and conflict as a very important aspect in human kind. Thus, religion tends to expurgate it from reality. This article will give an overview of these critics and which can be the main ways to answer them.